An accurate orientation measurement system of self-propelled artillery barrel based on coordinate system mapping. (1st November 2022) - Cheng, Zejun; Wang, Huaiguang; Han, Lanyi; Du, Binhan; Shi, Zhiyong
Abstract: Barrel orientation accuracy is an essential factor affecting the hit rate of self-propelled artillery, which comprehensively reflects the working state of the self-propelled artillery fire control system. An accurate self-propelled artillery orientation measurement system based on the coordinate system mapping is proposed to reduce the axis simulation error and introduce the north datum. The measurement system uses Radio Navigation Satellite System orientation technology to determine the measurement area's standard north orientation. Based on the standard north orientation, a coordinate measurement system is established. The total station and self-propelled artillery positions are unified to the coordinate measurement system. The total station measures the coordinates of the marked points on the barrel. According to the coordinates of the marker points under different datums, the mapping relationship of different coordinate systems can be obtained. The total station measures the azimuth and elevation angle of the line connecting the marked points. Based on the coordinate system mapping relationship, the accurate orientation of the self-propelled artillery barrel can be calculated. The combined standard uncertainty evaluation is performed, and the uncertainties of the azimuth and elevation angles are 1.5167 × 10 − 4  rad and 1.6341 × 10 − 4  rad, respectively. A particular type of self-propelled artillery is selected for experiments. The results show that the system's measurement accuracy can be guaranteed within 2.0944 × 10 − 4  rad .